Sigla (Sigla_V_XV) - Robinson, James M. (BrillOnline Reference Works, 2012)
A dot placed under a letter in the transcription indicates that the letter is visually uncertain, even if the context makes the reading certain. Letters having the superlinear stroke are also dotted when the superlinear stroke is lost in a lacuna. Dots on the line outside of brackets in the transcription indicate missing letters that cannot be restored but of which vestiges of ink remain. Three dots on the line in the translation indicate the presence of substantial untranslatable material